Faktor-Faktor yang Mempengaruhi Kelengkapan Pengisian Rekam Medis Rawat Inap di RSUD Kabupaten Sumedang Tahun 2011 - Arief Tarmansyah Iman (Jurnal Persada Husada Indonesia, 2015)
One of the vital information for SIRS is medical records. Medical records must be filled correctly andcompletely becauseitcontain vital information that covers administrative, legal, financial and clinical aspects. AtSumedang District Hospital in 2010, 74.8% inpatient medical records werefilled partly.The aim of this study istoanalyze the completeness of medical records at inpatient ward and the contributing factors. A mixed methodssequential explanatory research had been used.It started with a quantitative research for385medical records,followed by a qualitative research to describe the findings. Subjects consist of health officers from inpatientward and hospital managers, totalling13 people. The results showed that 58,4% inpatient medical records wereincomplete. This results consist of 23,9% Medical Resume, 30,3% Operation Report, 18,2% Identification ofInfants and 14.9% Labor Report. The contributing factors are input factor(lack of technical knowledge, negativeattitudes, inadequatefacilities, SOP, and socialization) and process factor (SOP, difference in treatment,monitoring and evaluation system not optimaland incoherent teamwork). The completeness of medical recordscan be improved by evaluating and monitoring the aforementioned factor.Keywords: completeness, medical record, inpatient ward.